(untitled) (Philological Studies, 2019)
Since 1991, Serbian citizens in the Republic of Croatia have held the status of a national minority, and the Serbian language is categorized as a minority language. Surprisingly, the population censuses of 2001 and 2011 have shown that only a quarter of Croatian Serbs listed Serbian as their mother tongue. Those censuses (as well as legal acts on minority language rights) do not reveal much about the actual language used by Croatian Serbs, but only reflect how they have listed their native language. This paper analyzes the language of literature written by Serbian writers from Croatia whose works were published after 1991 by the Serbian Cultural Society Prosvjeta’s publication company in the edition Mala plava biblioteka. Since their works reflect the tension between Deleuze’s and Guattari’s (1986) concept of a minor literature as a literature “that which a minority constructs within a major language” and the preservation of a minority language through literary production, this paper will analyze the collective and political values attributed to the literature written by Serbian writers from Croatia.